Evaluación sanitaria de expendios ambulantes de pescado en dos barrios de la ciudad De Bogotá (2019)
Eating fish can bring many health benefits because it contains essential nutrients for the body, such as excellent quality proteins and more lipids healthier than those contained in other foods. In addition, it is essential in a diet balanced, contributing, for example, to the prevention of cardiovascular diseases, which is why Fish consumption has increased considerably in recent years (Rengifo, 2015).